Paraquat poisoning: A case report and review of literature - Kondle Raghu; Vidavalur Mahesh; Parri Sasidhar; Polam R Reddy; Vajja Venkataramaniah; Amit Agrawal (Wolters Kluwer Medknow Publications, 2013)
Paraquat (1, r-dimethyl-4,4'-bipyridium dichloride), a brown syrupy liquid is an effective herbicide that has low chronic toxicity because of its rapid deactivation on contact with soil. A high dose of paraquat or severe poisoning has a poor prognosis. At present there is no specific antidote to paraquat poisoning, hence the need to focus on prevention and in case of exposure or ingestion, aggressive decontamination to prevent further absorption. Although uncommon, paraquat ingestion can lead to severe and often fatal toxicity. However, despite its widespread availability, reports of this herbicide poisoning in India are uncommon.